The landscape of chemokine and cytokine is associated with the distinct clinical status of leprosy patients and their respective household contacts - Pereira de Oliveira, Lorena Bruna; Marçal, Pedro Henrique Ferreira; Campos, Karolina Dias; dos Santos, Daisy Cristina Monteiro; Lima, Marlucy Rodrigues; Martins-Filho, Olindo Assis; Brito-de-Sousa, Joaquim Pedro; Abdala-Torres, Thais; Pinheiro, Roberta Olmo; Sarno, Euzenir Nunes; Fairley, Jessica K.; Fraga, Lucia Alves de Oliveira (Frontiers in Immunology, 2024)
IntroductionLeprosy, a chronic infectious disease, is closely linked to the host immune response. According to the WHO, leprosy patients (L) and household contacts (HHC) are classified into subgroups: paucibacillary (PB) and multibacillary (MB), witch reflect the degree of infection in patients and the level of exposure of their contacts. The main goal of this study was to: i) establish a comprehensive overview of soluble mediator signatures of PBMCs upon in vitro antigen-specific stimuli and ii) identify whether the chemokine (CH) and cytokine (CY) signatures were associated with distinct clinical manifestations in (L) and immune response profiles in (HHC).MethodsLong-term PBMC cultures were carried out and supernatants collected for 12 CH and CY analisys by Cytometric Beads Array.Results and discussionThe CH and CY analysis, using continuous variable modeling, demonstrated that PBMCs from both L and HHC exhibited high levels of TNF upon M. leprae-stimuli. While lower production of IFN-γ were observed for L, low levels of CXCL8 was found for HHC. Soluble mediator signatures, analyzed using categorical variables, revealed that while high levels of TNF were observed for L, high levels of IFN-γ appeared as a hallmark of HHC. Overall, these analyses demonstrated that CXCL8, IFN-γ, and TNF were key markers differentiating L from HHC and endemic control (EC), especially considering the categorical analysis of the soluble mediator signatures. Data further demonstrated that higher levels of IFN-γ and lower levels CXCL8 was features associated with HHC(MB), whereas high levels of TNF were observed in both L subgroups. Moreover, data from integrative networks, based on correlation amongst soluble mediators, revealed that in M. leprae-stimuli, the number of correlations was lower in HHC(MB) compared to HHC(PB), but higher in L(MB) compared to L(PB). It was noted that the number of correlations decreased in the following order: EC > L > HHC. Our findings contribute to additional immunological features associated with L and HHC, witch can be useful complementary diagnostic/prognostic tools for classification of L and HHC, providing insights to enrich the research agenda about the hypothesis that HHC should be closely monitored as they may present a subclinical infection.